2007
DOI: 10.1158/1078-0432.ccr-06-2894
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Directs the Accumulation of Interleukin-12–Induced IFNγ into Tumors for Enhancing STAT1–Dependent Antitumor Effect

Abstract: Purpose: To examine the mechanism by which doxorubicin plus interleukin-12 (IL-12) gene transfer induces enhanced therapeutic efficacy against tumors. Experimental Design: Tumor-bearing mice were treated with doxorubicin, IL-12^encoding plasmid DNA, doxorubicin plus IL-12^encoding plasmid DNA, or plasmid DNA control. Doxorubicin was systemically given via i.p. injection, and IL-12 was systemically expressed via i.m. injection.To show that doxorubicin enhances the accumulation of IL-12^induced IFNg into tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 46 publications
4
39
0
Order By: Relevance
“…Experimental studies have demonstrated that doxorubicin can augment immune responses that involve macrophage and NK cell activity (Ujhazy et al, 2003). It is noteworthy that antitumoral efficiency of some cytostatics, including doxorubicin, could be enhanced by coadministration of IFN␥ and an improved antitumor efficacy by coadministration of doxorubicin and IL-12 is dependent on the accumulation of IFN␥ in tumors (Wadler and Schwartz, 1990;Zhu et al, 2007). To date, detailed studies on the effects of doxorubicin on the pattern of tumor cell gene expression linked to immunomodulation or interferon signaling are not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have demonstrated that doxorubicin can augment immune responses that involve macrophage and NK cell activity (Ujhazy et al, 2003). It is noteworthy that antitumoral efficiency of some cytostatics, including doxorubicin, could be enhanced by coadministration of IFN␥ and an improved antitumor efficacy by coadministration of doxorubicin and IL-12 is dependent on the accumulation of IFN␥ in tumors (Wadler and Schwartz, 1990;Zhu et al, 2007). To date, detailed studies on the effects of doxorubicin on the pattern of tumor cell gene expression linked to immunomodulation or interferon signaling are not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor bearing were subject to control DNA (10 mg/mouse), control DNA plus doxorubicin (1 mg/kg), IL-12-encoding DNA (10 mg/ mouse), or IL-12-encoding DNA plus doxorubicin, and followed by electroporation as described previously. 50 Tumor volume was calculated by the formula:…”
Section: Animalsmentioning
confidence: 99%
“…Co-administration of IL-12 protein or gene with traditional chemotherapeutic drugs, such as paclitaxel and doxorubicin, inhibits tumor growth and extends the survival time of tumor-bearing mice. 9,10 However, these traditional chemotherapeutic drugs also kill or stop normal cells dividing rapidly, resulting in marked systemic side effects, such as hematopoietic toxicity. 11,12 In contrast, differentiation agents have less serious side effects because of their effect on the process of carcinogenesis that tend to make cancer cells revert back to more normal differentiation.…”
Section: Introductionmentioning
confidence: 99%